If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 2) + -1y = 2(y + -1) + 5 Reorder the terms: (2 + y) + -1y = 2(y + -1) + 5 Remove parenthesis around (2 + y) 2 + y + -1y = 2(y + -1) + 5 Combine like terms: y + -1y = 0 2 + 0 = 2(y + -1) + 5 2 = 2(y + -1) + 5 Reorder the terms: 2 = 2(-1 + y) + 5 2 = (-1 * 2 + y * 2) + 5 2 = (-2 + 2y) + 5 Reorder the terms: 2 = -2 + 5 + 2y Combine like terms: -2 + 5 = 3 2 = 3 + 2y Solving 2 = 3 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 2 + -2y = 3 + 2y + -2y Combine like terms: 2y + -2y = 0 2 + -2y = 3 + 0 2 + -2y = 3 Add '-2' to each side of the equation. 2 + -2 + -2y = 3 + -2 Combine like terms: 2 + -2 = 0 0 + -2y = 3 + -2 -2y = 3 + -2 Combine like terms: 3 + -2 = 1 -2y = 1 Divide each side by '-2'. y = -0.5 Simplifying y = -0.5
| 3c^3-192=1 | | abs(-1+3x)=7x+4 | | 3(4k+5)=-27+6k | | 3/5x+2=6 | | 2y+3y=55 | | 4(4k+5)=-27+6k | | 3+4e= | | -8(8p+6)=8-8p | | 3+5e= | | 6-2(x+1)=42 | | 2x+1x=7 | | 12x-4=36 | | 6-4(n-1)=2n+4 | | 6(4x+2)+4x= | | 3(-7+3x)(-6-6x)= | | 18/7= | | 9x=3(7x+24) | | 3[x-1]=7 | | x+0.05(x)=9.70 | | graphy=-7x-13 | | (3x+13)+10= | | 8x^4-18x^2+8x^4=0 | | 1a^2+3a=-2 | | 2x-(3x/2)=4 | | 115=8/5x | | 3xsquared-7=69 | | kx^2-9x+6=0 | | 4x+6=2(4+x)-2 | | x-8=6x-6 | | 3x=4y+-8 | | 6x^3-22x^2+9x=0 | | e^3x=6*e^3*x |